PUPUK BAYFOLAN DAN PUPUK KANDANG SAPI BERPENGARUH KEPADA PERTUMBUHAN DAN PRODUKSI SEMANGKA (Citrullus vulgaris Schard) - Dartius ,; Asritanarni Munar; Hermawan , (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2011)
AbstractThis study aims to determine the growth and production of watermelon caused by bayfolan fertilizer and manure cow used Group Randomized Design factorial with two factors. The results showed that the use of bayfolan fertilizers significant influence on all parameters except the observation of the fruit diameter. While the treatment of cattle manure only had a marked influence on the age parameters of harvest, and no significant effect on other parameters. For the interaction between the two treatments, namely the provision of bayfolan fertilizer and manure cow showed no significantly different effect on all parameters of the observations. Keywords: Citrullus vulgaris Schard, bayfolan fertilizer and cow manure